(untitled) (Revista Contexto & Saúde, 2024)
Information and Communication Technologies (ICT) encompass technical tools that facilitate the sharing of information and communication processes through resources such as computers, the internet, and social media. One significant tool provided by ICT is videos hosted on virtual platforms like YouTube®, which are increasingly adopted in health education as Active Methodologies replace the traditional Cartesian approach. This study aimed to analyze the content of videos on Intrauterine Device (IUD) insertion and lumbar puncture available on the YouTube® site, assessing the quality of the material published regarding the demonstration/execution of the aforementioned procedures. This is an exploratory-descriptive, documentary-type study. For the search on the IUD insertion procedure, the following descriptor was used: “IUD insertion”. For the second search, regarding the lumbar puncture procedure, the descriptor “lumbar puncture” was used in the YouTube® search field. In each search, the first 100 results were displayed After the initial search and data collection, a full viewing of all the videos selected for analysis was conducted. After applying the eligibility criteria, the final sample consisted of 45 videos, with 30 related to the IUD insertion procedure and 15 to the lumbar puncture procedure. Regarding the person responsible for producing the videos, for both procedures, the majority for both procedures were created by individuals in Brazil, typically in an outpatient setting using simulator-type resources. Based on the theoretical framework adopted in this study, it was found that 100% of the videos analyzed for both procedures did not follow the correct execution sequence. It is recommended that medical undergraduate students exercise greater caution and prudence when searching for and selecting audiovisual materials on digital platforms.